2009
DOI: 10.1210/me.2008-0168
|View full text |Cite
|
Sign up to set email alerts
|

PAPA-1 Is a Nuclear Binding Partner of IGFBP-2 and Modulates Its Growth-Promoting Actions

Abstract: IGF-binding proteins (IGFBPs) have multiple cellular effects, which occur by both IGF-dependent and -independent mechanisms. IGFBP-2 is involved in the regulation of both normal and carcinogenic cell growth. To further understand the actions of IGFBP-2, we carried out a yeast two-hybrid screen to search for intracellular partner proteins using a human prostate cDNA library. We isolated Pim-1-associated protein-1 (PAP-1)-associated protein-1 (PAPA-1) as an IGFBP-2-binding protein, whose expression and subcellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…17,20 IGFBP-2 was also reported to transmit signals independently of IGF-I/II by affecting cell adhesion via integrin binding, [21][22][23] and even to act in the cell nucleus. 24 In addition, increased levels of IGFBP-2 in the serum of cancer patients was shown in a variety of human cancers to be an indication of poor prognosis, [25][26][27][28][29] including CRC patients. [30][31][32][33] A recent study identified IGFBP-2 signaling as an important factor in the recruitment of endothelial cells in metastatic breast cancer by a miR-126-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…17,20 IGFBP-2 was also reported to transmit signals independently of IGF-I/II by affecting cell adhesion via integrin binding, [21][22][23] and even to act in the cell nucleus. 24 In addition, increased levels of IGFBP-2 in the serum of cancer patients was shown in a variety of human cancers to be an indication of poor prognosis, [25][26][27][28][29] including CRC patients. [30][31][32][33] A recent study identified IGFBP-2 signaling as an important factor in the recruitment of endothelial cells in metastatic breast cancer by a miR-126-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as a prognostic marker in prostate cancer, which suggests a link between this group of proteins and prostate carcinogenesis. INO80B induces growth arrest by halting the cell cycle at the G1phase (Miyako et al, 2009; Kuroda et al, 2004). The effect of the POP chemical HCB was studied in detail in NIH 3T3 (mouse) and WS1 (human) embryonic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IGFBP-2 has been reported to be localized on the cell surface, in the cytoplasm and on the nuclear membrane [14]. Several groups have now reported nuclear localisation of IGFBP-2 [15][16][17]. A functional nuclear localisation sequence in the central domain of IGFBP-2 has been reported that appears to interact with importin-α [18].…”
Section: Igfbp-2mentioning
confidence: 99%